Pengembangan Profesionalisme Guru Menurut Standar Regulasi: Upaya Meningkatkan Mutu Pendidikan - Cut Zuhraina; Raudatul Husna (Al-Musannif, 2022)
Technology’s fast and rapid development is not directly proportional to the development of teacher professionalism. Even changes in education policy based on the times have not been accompanied by efforts to develop teacher professionalism in Indonesia. This study aims to analyze teacher professionalism according to regulatory standards, models for developing teacher professionalism, and the implications of developing teacher professionalism for improving the quality of education. This literary research uses a pedagogic and juridical approach. Data were documented from relevant journals and books and then analyzed using content analysis techniques. The results of the study show that professional teachers must master learning approaches, models, methods, strategies, and tactics so that they can arouse students’ interest and willingness to learn. The importance of improving teachers’ professional abilities, in general, can be viewed from three perspectives: the development of science and technology, job satisfaction and morale, and work safety. Efforts to increase teacher professionalism must be carried out systematically, carefully planned, adhere to principles, and be evaluated objectively. This research has implications for efforts to increase teacher professionalism that should be carried out not only by school principals or the government, but most importantly by the teacher himself.